Propagation of Shear Horizontal Wave at Magneto-Electro-Elastic Structure Subjected to Mechanically Imperfect Interface - Anandakrishnan Akshaya; Santosh Kumar; Kulandhaivel Hemalatha (Mechanics of Advanced Composite Structures)
This study delves into the investigation of shear horizontal transverse waves within a structure composed of a layer and a semi-infinite medium. The layer considered in this work is made of functionally graded magneto-electro-elastic material, and the semi-infinite medium is comprised of functionally graded piezoelectric material with a linear gradedness parameter. Additionally, the layer and semi-infinite medium has a mechanical imperfect interface. Furthermore, the solutions for the layer and semi-infinite medium are derived utilizing the WKB approximation technique. This involves initially transforming the partial differential equation into an ordinary differential equation through basic variable separation and the ordinary differential equation is solved by WKB approximation technique. The obtained results lead to dispersion relations presented in determinant form for two cases: electrically open and short. To explore the influences of various parameters on shear horizontal transverse waves, a specific model is considered. This model is composed of a layer made of magneto-electro-elastic material (BaTiO3-CoFe2O4) and a semi-infinite medium consisting of piezoelectric material (BaTiO3). Also, the graphs are plotted to visualize the variation in shear horizontal transverse waves in relation to both phase velocity and wave number.